Outcomes of acute hepatitis B virus (HBV) in HIV infection with and without HBV-active antiretroviral therapy. (1st May 2021) - Falade-Nwulia, Oluwaseun; Seaberg, Eric C.; Snider, Anna E.; Rinaldo, Charles R.; Wolinsky, Steven M.; Witt, Mallory D.; Thio, Chloe L.
Abstract : N/A: Men with acute hepatitis B virus (HBV) infection in the Multicenter AIDS Cohort Study from 1985 to 2013 had serological testing to determine proportions with HBV recovery or chronic hepatitis B (CHB). A similar proportion of men without human immunodeficiency virus (HIV) and men with HIV receiving HBV-active antiretroviral therapy (ART) developed CHB [8.2%, 95% confidence interval (CI) 3.8–15.0% vs. 7.7%, 95% CI 2.00–36.0%]. In contrast, 17.5% (95% CI 8.7–29.9%) of men living with HIV, not on HBV-active ART developed CHB. HBV-active ART protects against developing CHB. Abstract : Supplemental Digital Content is available in the text